2023
DOI: 10.1200/jco.22.01064
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Exemestane With Ovarian Suppression in Premenopausal Breast Cancer: Long-Term Follow-Up of the Combined TEXT and SOFT Trials

Abstract: Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. The combined analysis of SOFT-TEXT compared outcomes in 4,690 premenopausal women with estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 17 publications
0
41
0
4
Order By: Relevance
“…Similarly, the 12 year update from the pivotal SOFT and TEXT trials, which randomized premenopausal women with HRþHER2-disease to adjuvant tamoxifen, tamoxifen plus ovarian suppression, or exemestane plus ovarian suppression, was published this year. These reports continue to show benefit in DFS from the addition of ovarian suppression, benefit in DFS from use of exemestane over tamoxifen with ovarian suppression, but no OS benefit of using exemestane instead of tamoxifen [37,38].…”
Section: Breast Cancer In Pre-menopausal Womenmentioning
confidence: 97%
“…Similarly, the 12 year update from the pivotal SOFT and TEXT trials, which randomized premenopausal women with HRþHER2-disease to adjuvant tamoxifen, tamoxifen plus ovarian suppression, or exemestane plus ovarian suppression, was published this year. These reports continue to show benefit in DFS from the addition of ovarian suppression, benefit in DFS from use of exemestane over tamoxifen with ovarian suppression, but no OS benefit of using exemestane instead of tamoxifen [37,38].…”
Section: Breast Cancer In Pre-menopausal Womenmentioning
confidence: 97%
“…500 Patientinnen ist die Fallzahl eher klein für die adjuvante Situation. Die Vergleichsgruppe (SOFT/TEXT) wurde mehr als 10 Jahre vor der POSI-TIVE-Studie rekrutiert [67]. Die Behandlung hat sich in dieser Zeit jedoch verändert, sodass der Vergleich mit diesen Studien unter Umständen schwierig ist.…”
Section: Schwangerschaften Bei Patientinnen Nach Hormonrezeptorpositi...unclassified
“…Consequently, the authors suggest that OFS should be considered in selected cases in combination with exemestane (over tamoxifen plus OFS) mainly in cHR patients and should be offered for 5 years. 22,35 The ASTRRA trial demonstrated positive results in eventfree survival with 2 years of treatment with tamoxifen plus OFS. This finding suggests that adding OFS to TAM should be considered for those who remain in a premenopausal state or resume ovarian function after N/ACT and longer follow-up is needed to fully evaluate the OS benefit.…”
Section: Adjuvant Endocrine Therapymentioning
confidence: 99%